2014
DOI: 10.1007/s11136-014-0791-8
|View full text |Cite
|
Sign up to set email alerts
|

Content verification of the EORTC QLQ-C30/EORTC QLQ-BR23 with the International Classification of Functioning, Disability and Health

Abstract: This study demonstrates that the content of the EORTC QLQ-C30 goes beyond functioning and includes global feeling of well-being and that the content of the EORTC QLQ-BR23 is related to functioning. Furthermore, linking items to the ICF framework could be an additional method to validate the content of health-related questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…While we did not include this 30-item measure, its content has been shown to capture 25 domains related to symptoms and function and also includes three questions, one each on health perception, overall QOL rating, and financial impact of cancer [55]. The functional domains on the EORTC Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not include this 30-item measure, its content has been shown to capture 25 domains related to symptoms and function and also includes three questions, one each on health perception, overall QOL rating, and financial impact of cancer [55]. The functional domains on the EORTC Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse events were graded based on the National Cancer Institute Common Terminology Criteria for Adverse Events (NCI CTCAE) version 4.03 . QOL was evaluated using the European Organization for Research and Treatment of Cancer Quality of Life of Questionnaire (EORTC QLQC30) questionnaire at study entry, and prior to surgery . In addition, the parameters of tumor metabolism and blood supply, as demonstrated by PET and DCE‐MRI, were collected and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…One study 40 assessed the content validity of the EORTC QLQ-C30 based on the opinions of 21 experts. When mapping to the WHO's International Classification of Functioning (ICF) framework, 25 of the 30 items in the EORTC QLQ-C30 were endorsed by the experts: 15 items mapping to impairment of body function, 7 mapping to activity limitations/participation restrictions, and 1 item mapping to both components.…”
Section: Assessment Of Validity Reliability and Responsivenessmentioning
confidence: 99%
“…The authors stated that the fact that most items from the EORTC QLQ-C30 can be linked to the ICF framework means that the instrument's content reflects functioning, which is a key component of HRQoL. 40 No studies were identified that investigated the validity, reliability, or responsiveness of the EORTC QLQ-C30 among patients with earlystage TNBC. Among patients with metastatic breast cancer, a 1997 study investigated the inter-rater reliability using patient-observer agreement on the EORTC QLQ-C30 questionnaire.…”
Section: Assessment Of Validity Reliability and Responsivenessmentioning
confidence: 99%